2017
DOI: 10.18632/oncotarget.19453
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and survival prognosis of prostate cancer in patients with end-stage renal disease: a retrospective study based on the Korea national database (2003-2010)

Abstract: ObjectiveThe study was aimed to evaluate the prevalence and prognosis of prostate cancer (PC) and end-stage renal disease (ESRD), determine the risk factors for overall survival (OS) and PC-specific survival (CSS), and evaluate differences in PC-related clinical therapeutic patterns between patients with and without PC-ESRD.MethodsThis observational population study, performed at the National Cancer Center and Cancer Research Institute in Korea, included patients with PC and ESRD from the nationwide Korean Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Many countries have analyzed various diseases in the field of urology using national insurance data [ 3 4 5 ]. Several multicenter studies on urological diseases have been conducted in Korea, but national survey or population-based studies are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Many countries have analyzed various diseases in the field of urology using national insurance data [ 3 4 5 ]. Several multicenter studies on urological diseases have been conducted in Korea, but national survey or population-based studies are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Therefore, a large number of patients with high risk and advanced disease were enrolled in study. However, this patient distribution differs from that in contemporary series of renal transplant candidates, of whom 91% with newly diagnosed prostate cancer are in the low risk group 8 and overall survival is mainly predicted by kidney function status. Median survival in patients on hemodialysis is less than 10 years and probably less than 5 years in the presence of associated morbidities (ie diabetes and heart failure).…”
Section: Immunosuppression In Renal Transplantmentioning
confidence: 60%
“…Kim et al evaluated the pattern and prognosis of prostate cancer in 3,945 patients with ESRD. 8 Most of these patients were at low risk, including 91% with cT1c, Gleason grade 6 and pT2 after RP, with 100% recurrence-free survival. Kim et al found that in these patients it was mainly kidney function status rather than prostate cancer which determined survival.…”
Section: Immunosuppression In Renal Transplantmentioning
confidence: 93%
“…Previous studies have shown that localized PCa is the most common presentation of PCa in dialysis patients. 14 , 15 Since localized PCa is asymptomatic, it is likely that the majority of the cases, especially those in the low‐risk group, were diagnosed during screening. Despite the controversy around screening with PSA even in the general population, dialysis patients who are getting evaluated for a KT undergo screening with PSA at a very high rate of 89% during their evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that localized PCa is the most common presentation of PCa in dialysis patients. 14,15 Since localized PCa is asymptomatic, it is likely that the majority of the cases, especially those in the low-risk group, were diagnosed during screening.…”
Section: Discussionmentioning
confidence: 99%